Tanggung Jawab Tertundanya Pembayaran Pajak Para Pelaku Usaha Tempat Hiburan Malam Dimasa Pandemic Covid-19 - Hidayat, Indra; Marpaung, Devi Siti Hamzah (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2021)
The outbreak of covid-19 causes a variety of problems in the community, where this outbreak also has a bad impact on the economic sector both central and regional where this affects the payment of taxes for taxpayers in Indonesia. Because of the many sectors affected by this outbreak that affect the sources of income of businesses are no exception for businesses nightlife venues, because of this outbreak and the enforcement of restrictions on hours and also the policy of psbb the night entertainment businesses get a pretty bad impact where they have to pay the salaries of their employees they are also harmed because they have to accept that their turnover decreased during the outbreak this hit Indonesia so that because the application of taxes from the huburan is quite high, so they will be quite burdened with the dependents they have by having to pay taxes. Thus things such as delayed payment of taxes are inevitable. With the explanation of these things, this study will explain how responsibility for businesses as a result of the delayed payment of entertainment tax.